Flooding regime drives tree community structure in Neotropical dry forests. (14th September 2019) - Araújo, Felipe De Carvalho; Tng, David Yue Phin; Apgaua, Deborah Mattos Guimaraes; Morel, Jean Daniel; Pereira, Diego Gualberto Sales; Santos, Paola Ferreira; Santos, Rubens Manoel dos
Abstract: Questions: Riverine and associated vegetation communities are periodically affected by floods. However, there have been few quantitative studies on the structural responses of Neotropical tree communities in semi‐arid regions to this perturbance. Here, we ask whether flooding regimes and soil attributes affect tree species diversity, composition, community structure, and soil attributes in Neotropical dry forests. Locations: Southeast Brazil. Methods: We sampled 120 forest plots of 400 m² totaling 4.8 ha across four tributaries of the São Francisco River with plots situated in areas representing three flooding regimes: (a) annually flooded; (b) occasionally flooded; and (c) never subjected to flooding. Using linear mixed‐effects models, we modelled how flooding regime and soil properties (fertility and texture) affect vegetation diversity (species richness), species composition and structural attributes (abundance of individuals, above‐ground biomass [AGB], and a community‐weighted trait average of multistemness [CWMms ]) of these forest plots. Results: Species richness in the annually flooded forests was significantly lower than in occasionally flooded or never flooded forests, in agreement with our models, which showed that flooding regime was a significant predictor for this variable. Flooding regime was a significant predictor of CWMms, with plots in annually flooded forest sites having the highest CWMms values. Soil chemical attributes were a significant predictor of AGB across all plots but not between flooding regime categories. Conclusions: In Neotropical dry forests, environmental filters established by flooding can lead to differences among distinct biomes in vegetation structure, diversity patterns as well as system productivity. Conservation strategies for dry forests should therefore take these factors into consideration. Our study also highlights annually flooded dry forest as a significant component of the regional diversity of dry forests deserving of management attention. Abstract : Neotropical dry forests proved to be a part of a distinct and threatened global biome housing a diverse adapted dry forest flora along a water availability gradient. Flooding and soil uncovered intriguing patterns of structure, which we report for the first time highlighting ecological differences of these patterns relative to flooded forests in other moist biomes.